Fractioned drilling: a technique for wedge osteotomy of the knee - Sabo, Desiderius; Flierl, Steffen Werner; Thomsen, Marc N.; Cotta, Horst (International orthopaedics, 1995)
High tibial wedge osteotomies are often followed by transient neurological complications. From a retrospective study of 132 patients it appears that the incidence of this troublesome complication can be reduced after osteotomy with external fixation by using a technique of making consecutive drill holes of increasing diameter followed by osteoclasis. This reduction of neurological complications was most marked when a less extensive surgical approach was used.